How do financial contracts evolve for new ventures? - Fu, Danying; Jenkinson, Tim; Rauch, Christian (Journal of Corporate Finance, 2023)
While previous research has characterized the key features of contracts between entrepreneurs and venture capitalists, little is known about the contracts' evolution over time and across funding rounds. We overcome significant data challenges to compile a novel panel dataset of U.S. early-stage ventures that includes the main financial and control rights offered to investors at each (equity) funding round. We find that there is a ‘default contract’ with a distinct combination of rights that the majority of companies gravitate to. This default contract is typically implemented in the initial Series A funding round and rarely deviated from in later rounds. Whenever deviations do occur, terms are usually revised in favour of investors, and not entrepreneurs. Due to this stickiness of the default contract, for successful startups we argue that post-money valuations in later rounds can be a reasonable proxy for the economic value of the firm.